Information security and optimization - Tanwar, Rohit; Choudhury, Tanupriya; Zamani, Mazdak; Gupta, Sunil, 1979- (Boca Raton : C&H\CRC Press, 2021)
"Maintaining a practical perspective along with theoretical explanations, Information Security and Optimization explores the concepts that are essential for academics as well as organization's point of view. The book covers the definitions, discussion, working, and analysis of techniques and tools that are useful for a scholar ranging from beginners to experts. What are the policy standards, what are vulnerabilities, how to patch them, How to transmit data securely, how to secure data on the cloud, cryptocurrency and blockchain, optimization algorithms, and etc. are some of the possible queries that have been described effectively using examples from real life and case studies. Features: A wide range of case studies and examples that are derived from real-life scenarios that map the theoretical explanations with real incidents. Description of security tools related to digital forensic with their unique features and the working steps for hands-on experience. Novel contributions in designing organization security policies and lightweight cryptography. Presents real-world use of blockchain technology and biometrics in cryptocurrency and personalized authentication systems. Discussion and analysis of security in the cloud that needs focus because of extensive use of cloud services for serving organizational and research demands including data storage and computing requirements. The book Information Security and Optimization is equally helpful for the undergraduate and postgraduate students as for the researchers working in the domain. It can be recommended as a reference or textbook for the courses related to cybersecurity"--
Information security policy and standards / Samir Pawaskar -- Vulnerability management / K.N.D. Saile, Phani Kumar Gajula -- Identity theft and prevention / A. Tajpour, M. Zaman -- Organization security policies and their after effects / Premkumar Chithaluru, Ravi Prakash -- Cyber attacks and their impact on real life / Premkumar Chithaluru, Rohit Tanwar, Sunil Kumar -- Cryptography and steganography techniques / Ninni Singh, Gunjan Chhabra -- An FPGA-based advanced lightweight cryptography architecture for iot security and its cryptanalysis / Rajdeep Chakraborty, Jyotsna Kumar Mandal -- An overview of digital image forensics : image morphing & forgery detection algorithms / Rahul Chauhan, Preeti Mishra, R.C. Joshi -- Analysis of classification based intrusion detection techniques / S.Sridevi, R.Anandan -- Cryptocurrency and blockchain / Premkumar Chithaluru, Kulvinder Singh, Manish Kumar Sharma -- Cyber security in cloud platform / Shiv Dutta Mishra, Bhupesh Kumar Dewangan, Tanupriya Choudhury -- Biometrics-unique identity verification system / G. Chhabra, V. Sapra, N. Singh -- Security tools / Keshav Kaushik, Rohit Tanwar, A.K. Awasthi -- Introduction to optimization algorithms-bio inspired / Rakesh Kumar Saini, Shailee Choudhary, Anupam Singh, Amit Verma.
OCLC-licensed vendor bibliographic record.
Keywords: Information technology -- Security measures; Computer security; Data encryption (Computer science); Mathematical optimization; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Cryptography; COMPUTERS / Internet / Security